Compact Planar Hybrid Ring Coupler With Embedded Meander Line - Abd Halim, Mohd Hafiz (Universiti Sains Malaysia, 2018)
Hybrid coupler can be used to decouple and increase the isolation between antenna ports. It is normally used in applications such as antenna feed networks, power dividers, combiners, mixers and digital phase shifters. In this project, it is focuses on how to design compact planar hybrid ring coupler with embedded meander line by using CST. The proposed of hybrid ring coupler is because it have better in terms of low production cost than other techniques, good return loss and isolation performances and reduce the cost. Thus, it can makes the device to perform with better performance. In this work, it is mainly focused on how to reduce the size of hybrid ring coupler so that it will obtain good S-Parameters readings. The proposed design is fabricated using Rogers RO4003C printed circuit board with dielectric constant of